Microstructural and mechanical characterizations of weld metal of S960QL ultra high strength steel joints obtained with different multi-pass laying techniques using GMAW - Mert, Tolga; Gurol, Ugur; Tumer, Mustafa (IOP Publishing Ltd, 2024)
15 mm thick ultra-high strength steel plates with 960 MPa yield strength were welded using different multi-pass laying techniques (i.e., stringer and weaving beads) with torch manipulation. Weld metals obtained were compared using different mechanical (i.e., micro tensile tests and Vickers hardness maps) and microstructural (i.e., optical microscope, scanning electron microscope, x-ray diffraction, electron backscatter diffraction) characterization techniques. Coarser grains and acicular ferrite were observed in weld metal obtained with the weaving pass procedure. There were hardness differences in the face and root passes of both weld metals. Yet, hardness values were 19% and 11% higher for the face and root regions of the joint obtained by stringer pass procedure, respectively. Fractographs of micro tensile test specimens revealed dimples depicting ductile network structure for both joints.
Keywords: UHSS; GMAW; weaving and stringer pass; characterization; EBSD; EVOLUTION; WIRE; Materials Science